Acupuncture treatment on attention deficit hyperactivity disorder: A protocol for systematic review and meta-analysis. Issue 34 (27th August 2021) - Xing, Liwei; Ren, Zeqin; Yue, Xianwu; Chen, Hongxi; Xia, Chunlin; Liu, Fan; Dong, Qinzuo; Wu, Kenan; Zhao, Rong
Abstract: Background: Attention Deficit Hyperactivity Disorder (ADHD) is the most common behavioral disorder in childhood. Acupuncture treatment of ADHD has formed a relatively systematic theoretical and clinical treatment system which achieved satisfactory results. However, there has been no systematic evaluation of its effectiveness and safety. The purpose of this study was to evaluate the efficacy and safety of acupuncture in the treatment of ADHD. Methods: A systematic search of literature will be conducted in PubMed, Cochrane Library, the Web of Science, Excerpt Medica Database, Chinese Biomedical Literature Database, VIP, Wanfang database, China National Knowledge Infrastructure database for articles published up to September, 2019. The searching terms include "attention deficit", "hyperactivity", "mild brain dysfunction", "acupuncture", "electroacupuncture". The search is limited to studies published in Chinese and English. Two reviewers will extract and evaluate the information independently. Cochrane Collaboration tool and Jadad scale will be used to evaluate the quality of the studies. Review Manager Version 5.3 (Cochrane Collaboration's software) will be used to carry out the meta-analysis. Results: High-quality synthesis and/or descriptive analysis of current evidence will be provided from effective rate, total score of traditional Chinese medicines syndromes, conners child hyperactivity-diagnosis rating scale, conners index of hyperactivity, the recurrence rate, and adverse events. Conclusion: This study will provide the evidence of whether acupuncture is an effective and safe intervention to ADHD. INPLASY registration number: INPLASY202140022